Komunikasi Antar pribadi Guru BK Dan Siswa Dalam Mengatasi Kenakalan Remaja: (Spiritual Counseling di SMK Ketintang Surabaya) - Dessy Dwi Lestari; Ellyda Retpitasari (Connected: Jurnal Ilmu Komunikasi, 2020)
This study aims to determine how counseling guidance teachers can overcome juvenile delinquency through interpersonal communication with spiritual counseling techniques. This research uses a qualitative approach with the type of phenomenological research. The subjects of this study were 5 students of SMK Ketintang Surabaya. In general, the findings of this study indicate that students are able to increase their resilience through spiritual counseling provided by counseling guidance teachers (BK). This method can raise awareness for students to always think positively and be able to accept their condition in any form, and any violations committed by students of the counseling teacher can provide punishment in the form of things that are beneficial to themselves and to get closer to the creator such as praying dhuha and reading letters yasin. Because the spirituality of these students is still low, so they still need guidance and direction from someone who is considered more mature and understands religious sciences.